Implementasi Perhitungan Harga Pokok Produksi dengan Menggunakan Metode Full Costing pada UMKM Warga Gunung Putri - Muhammad Renvil; Tania Alexandra Thiodora; Achmad Mahmuri; Arief Rachman; Erna Elsawati; Selvian Zai; Ventty Krisna; Aldi Pebriansyah; Iis Dewi Herawati (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Educational activities to be able to improve skills in calculating the cost of goods manufactured is a Community Service program carried out in Gunung Putri Village. This activity aims to provide education to develop an understanding of the concept of financial management in business. Broadly speaking, by learning about HPP (Cost of Goods Manufactured) residents can control costs that are not needed and increase production efficiency. With this education, it is hoped that MSMEs in Gunung Putri Village will have knowledge that can help determine competitive selling prices and the desired amount of profit. The results of the activity are very good because each factor is influential in realizing the success of education about the implementation of the calculation of the cost of goods manufactured using the full costing method in Gunung Putri Village in a directed and clear manner.